2010
DOI: 10.1021/es100164c
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Biases of Volunteer Water Quality Data

Abstract: State water quality monitoring has been augmented by volunteer monitoring programs throughout the United States. Although a significant effort has been put forth by volunteers, questions remain as to whether volunteer data are accurate and can be used by regulators. In this study, typical volunteer water quality measurements from laboratory and environmental samples in Iowa were analyzed for error and bias. Volunteer measurements of nitrate+nitrite were significantly lower (about 2-fold) than concentrations de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 26 publications
(36 reference statements)
2
46
0
Order By: Relevance
“…) to calculation of total nitrogen concentration in water (Loperfido et al. ). We extracted quantitative statistical results for each comparison.…”
Section: Methodsmentioning
confidence: 99%
“…) to calculation of total nitrogen concentration in water (Loperfido et al. ). We extracted quantitative statistical results for each comparison.…”
Section: Methodsmentioning
confidence: 99%
“…The United States has nearly 900 volunteer-monitoring initiatives that conduct scientific investigations in conjunction with governmental agencies, generally as a professional public-private partnership (EPA 1998). The objectives for such volunteer monitoring activities range from educational outreach to the generation of data used for regulatory purposes (Loperfido et al 2010, Mackechnie et al 2011. Quality assurance and documentation requirements for these data vary, depending on the ultimate use of the information.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…A number of previous studies have assessed the reliability of stream monitoring by volunteers in relation to professionals (Reynoldson et al 1986, Penrose and Call 1995, Au et al 2000, Fore et al 2001, Engel and Voshell 2002, Nicholson et al 2002, Nerbonne and Vondracek 2003, Sharpe and Conrad 2006, Gowan et al 2007, Loperfido et al 2010, Shelton 2013, Coates 2013, Moffett and Neale 2015. Most have concluded that, with appropriate resourcing and robust protocols, volunteer data agree closely enough with professional data for use in government http://www.ecologyandsociety.org/vol21/iss4/art32/ Involving community members in monitoring increases not only their ability to contribute data, but also their ability to discuss their knowledge with experts (described as "interactional expertise" by Carolan 2006).…”
Section: Introductionmentioning
confidence: 99%